Project ABC: Bridging tensions between institutional logics of care and business in healthcare - Conceição, A.; Major, M.; Clegg, S. (13th Conference on New Directions in Management Accounting, 2022)
In this paper we present an analysis of how activity-based costing (ABC) was included amongst austerity policy prescriptions within the healthcare sector. Relying on the proposition that an increasing quality of outcomes is achievable simultaneously with a reduction in costs, ABC straddles tensions between the logics of care and business. We draw on case study research and use institutional logic and related approaches that draw on paradox theory to analyze how the introduction of ABC became a device that made better cross-sectional communication between administrators and clinicians possible. When actor’s interests and power were aligned ABC was able to offer professional clinicians value in the hospital in question.